2022
DOI: 10.3389/fmicb.2022.950773
|View full text |Cite
|
Sign up to set email alerts
|

Multigene phylogeny, phylogenetic network, and morphological characterizations reveal four new arthropod-associated Simplicillium species and their evolutional relationship

Abstract: Simplicillium species are widely distributed and commonly found on various substrates. A minority of species are associated with arthropods. A spider-associated species Simplicillium araneae, and three insect-associated species, Simplicillium coleopterorum, Simplicillium guizhouense, and Simplicillium larvatum, are proposed as novel species based on a multi-locus phylogenetic analysis and morphological characteristics. These Simplicillium species completely fit the nutritional model of Hypocreales fungi and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…We also performed amplicon sequencing analysis of the fungal ITS region using the DNA samples extracted from the hind tibiae and the eggs (Table S2). Molecular phylogenetic analyses based on these sequen ce data consistently revealed that (i) the majority of the fungi were placed within the class Sordariomycetes of the Ascomycota, (ii) the majority were classified to the family Cordycipitaceae mainly consisting of entomopathogenic fungi such as Cordyceps , Beauveria and others (10,11), and (iii) the majority represented several specific fungal lineages such as Lecanicillium , Simplicillium and Akanthomyces (1214) (Figs. S4 and S5; Note S1).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…We also performed amplicon sequencing analysis of the fungal ITS region using the DNA samples extracted from the hind tibiae and the eggs (Table S2). Molecular phylogenetic analyses based on these sequen ce data consistently revealed that (i) the majority of the fungi were placed within the class Sordariomycetes of the Ascomycota, (ii) the majority were classified to the family Cordycipitaceae mainly consisting of entomopathogenic fungi such as Cordyceps , Beauveria and others (10,11), and (iii) the majority represented several specific fungal lineages such as Lecanicillium , Simplicillium and Akanthomyces (1214) (Figs. S4 and S5; Note S1).…”
Section: Resultsmentioning
confidence: 88%
“…S9c, d). These results suggest that adult females of M. gracilicorne preferentially pick up relatively benign entomopathogens, Simplicillium or Lecanicillium (1214,25,26), from environmental sources and selectively maintain them on the hindleg organ (Note S3).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The hosts of Akanthomyces species cover Hemiptera , Coleoptera , Lepidoptera , Orthoptera and Araneae ( Hodge 2003 ; Mongkolsamrit et al 2018 ; Chen et al 2020b , 2022c). Chen et al (2022b) noted that a host jump may be common in Simplicillium species, the spider-associated species may have originated from insects and then jumped to a spider host. An abundant diversity in insects and spiders has been discovered at Jinyun Mountain ( Huang and Zhang 1991 ; Li et al 2009a , 2009b ; Wang et al 2012 ; Huang et al 2021 ; Yan et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, based on multi-gene phylogenetic analyses, Simplicillium was shown to belong to the family Cordycipitaceae (Hypocreales, Hypocreomycetidae, Sordariomycetes) [14][15][16]. Within the genus Simplicillium, species have been delineated mainly by means of ribosomal RNA operon sequence analyses [17,18].…”
Section: Introductionmentioning
confidence: 99%